« Mais la loi ne fait pas tout » : l’homophobie dans la société française contemporaine depuis 2004 - Steve Wharton (Cahiers du MIMMOC)
Almost five years after France’s recognition of gay couples through the passage and enactment of the ‘PaCS’ (Pacte Civil de Solidarité), the French State broke new ground in December 2004 through a piece of legislation protecting French gays, lesbians, bisexuals and transsexuals against homophobia. Unlike the PaCS, the British equivalent measure, the ‘Civil Partnership’, in existence since December 2005, applies only to homosexual couples. For the first time ever, a legislative text condemns homophobia, as it amends a late 19th century Act on the freedom of the press (loi du 29 juillet 1881). The right to privacy, as defined in Article 9 of the Code Civil, found itself reinforced as a result of the new legislation, while the publication of homophobic texts was further restricted. But what about homophobic actions? This article’s aim is to put the new law into a wider context, in order to determine whether the situation of gays, lesbians, bisexuals and transsexuals has improved since the enactment of the PaCS. After going through a few key principles, this article will analyse the implication of the new law in relation with the gay wedding of Bègles (2004). Finally, before moving on to the conclusion, SOS-Homophobie, an organisation combating homophobic harassment will be surveyed, in a national context of continuing assaults against gays. In the light of the seemingly current homophobic backlash, does the new legislation really offer a better protection of the so-called gay community?